(untitled) (Journal of Governance and Development (JGD), 2023)
This study is to determine whether married women working in the public sector are able to sustain work-life balance and to elicit their views and suggestions on the support system needed to improve their work-life balance. This study adopts a quantitative method. Surveys were used as the main tool to gather data from seventy-six (76) women working in various public sectors in Komplek Tun Abdul Razak (KOMTAR) Penang. The study discovers that in general, married women working in public sectors are able to sustain worklife balance. The main support is the spouses who often help the women with their housework. However, most of the housework is done during weekends because of the limited time during the working days. The respondents agree that they are also able to spend good quality time with their families. The support system suggested by the respondents to promote work-life balance includes leave policies, flexible working hours, childcare centers and nursery room facilities at workplaces. Services suggested are Employee Assistance Program (EAP), counseling services and series of trainings for public sector employees in providing skills and knowledge to improve work-life balance.